"Fleeing Ideas" (IIF): reflections on a participatory budget experiment, in Italy's Bollate prison - Pittella, Giorgio (2022)
The essay reflects on the first outcomes of a pioneer experiment of participatory budgeting (PB) in the experimental detention centre of Milan - Bollate, coordinated by BiPart social enterprise and named by detainees “Idee in fuga”, which aimed to collect and progressively refine ideas of interventions and projects made by prisoners for their benefit, while intensifying the relationship between them and the prison administration. The democratic practice – monitored through three surveys, completed by interviews to participants – hinged on the respect for detainees’ self-organizational and self-determination capacity in elaborating proposals of high quality, that could favour a major convergence of future external funding and support actions felt meaningful by the convicted community. The essay’s focus is the analysis of the projects emerged from the deliberative phase of the process involving the detainees, and the phases of “appreciation and support” and voting of those ideas by the community of around 1200 inmates. Due to the unbalances existing among male and female sections of the detention centre, the project built two parallel participatory processes separated by gender, assuring to both communities a certain budget autonomy. Despite the complex rules of the prison, a series of inter-ward assemblies were made possible, to compensate the usual impossibility of different groups of detainees to communicate with each other and make a community-wide single PB process possible. 58 proposals, and their transformation into 10 more polished projects, are analysed, reorganising them in clusters referred to ideas focussed (1) on the transformation of internal facilities, (2) on programmes intended to bridge with the “future life of inmates after the end-of-sentence”, and (3) on transformations in the governance or regulations of the prisons. The visible difference between the types of proposals emerged in male and female wards (and more supported in each one) point out to the role played by the disparity of physical conditions between the two.